2004
DOI: 10.1128/jcm.42.8.3635-3643.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Hospital-Associated and Community-Acquired Clostridium difficile Infection in a Swedish County

Abstract: All episodes of Clostridium difficile associated diarrhea (CDAD) diagnosed in a defined population of 274,000 including one tertiary and two primary hospitals and their catchment areas were studied during 12 months. The annual CDAD incidence in the county was 97 primary episodes per 100,000, and 78% of all episodes were classified as hospital associated with a mean incidence of 5.3 (range, 1.4 to 6.5) primary episodes per 1,000 admissions. The incidence among hospitalized individuals was 1,300-fold higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
8
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 61 publications
6
121
8
1
Order By: Relevance
“…The analysis of hospital characteristics is particularly useful, since most CDAD cases are acquired while patients are hospitalized [15]. Significant correlations between ' high CDAD ' hospitals and facilities that admit large numbers of patients with other bacterial pathogens and other common infections was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of hospital characteristics is particularly useful, since most CDAD cases are acquired while patients are hospitalized [15]. Significant correlations between ' high CDAD ' hospitals and facilities that admit large numbers of patients with other bacterial pathogens and other common infections was noted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent county-level evaluation in Sweden revealed that hospital-acquired CDAD is 1300 times more common than community-acquired infections [15]. Thus, effective prevention and control measures are needed to reduce acquisition of CDAD.…”
Section: Introductionmentioning
confidence: 99%
“…[23]). From previous geographically localised studies in Sweden in 1999 to 2001, the six most common types were 014/SE21, 012, 001, 020, 002 and 005 [2][3][4]. All these were still among the most common types in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…We found decreased susceptibility mainly in types 012, 017, 046 and 231/SE37. Type 012 is related to serogroup C [29] and has been reported as a common type in Sweden, Greece and Hungary [2,19] while toxin A-negative, toxin B-positive type 017 has been found to be associated with outbreaks in, for example, Poland, Canada and the Netherlands [6,30]. Regarding type 231/SE37, the proportion of this type was 0.8 % at the Karolinska University Hospital, Huddinge, Sweden, in 1999 [4], but there is no information on whether this type has caused any outbreaks in other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation